The Quality of Leadership: A Model of Merit-Based Culture in East Borneo - Muadin, Akhmad; Akmalia, Rizky (Idarah (Jurnal Pendidikan dan Kependidikan), 2022)
Abstract: A successful educational institution depends on effective leadership. To close the achievement gap between high-performing schools and low-performing schools, principals are essential players. The purpose of this study is to identify the principal's leadership position in creating an accomplishment culture at SMA Negeri 1 Anggana. This study's methodology employs a qualitative descriptive paradigm. Data were gathered using observational, documentation, and interview methods. Condensing data, presenting data, and drawing inferences or performing verification are the processes taken during the data analysis stage. The outcomes demonstrated the principal's democratic leadership approach. The outcomes of identifying a leader's style include their personality/example, communication skills, ability to make decisions, and ability to inspire adherents. Abstak: Kepemimpinan yang efektif akan menjadi penopang dalam keberhasilan suatu lembaga pendidikan. Kepala Sekolah berperan fundamental mengatasi kesenjangan antara sekolah yang berprestasi tinggi dengan sekolah berprestasi rendah. Penelitian ini bertujuan untuk mengetahui peran kepemimpinan kepala sekolah dalam pengembangan budaya berprestasi di SMA Negeri 1 Anggana. Metode dalam penelitian ini menggunakan paradigma kualitatif jenis deskriptif. Data dikumpulkan melalui teknik wawancara, observasi, dan studi dokumentasi. Tahap analisis data dilakukan melalui serangkaian langkah terdiri dari kondensasi data, menyajikan data, dan menarik simpulan atau verifikasi. Hasil penelitian menunjukkan gaya kepemimpinan kepala sekolah identic dengan kepemimpinan demokratis. Hasil identifikasi terhadap gaya kepemimpinan antara lain kepribadian/keteladanan, kemampuan berkomunikasi, kapasitas pengambilan keputusan, dan kemampuan memotivasi bawahan.